Power-Based Political Economy in Persatuan Islam (Persis) Sects in Sapeken, Sumenep-Madura - Dodi, Limas (Madania: Jurnal Kajian Keislaman, 2021)
This research describes the phenomenon of contestation between the religious sects of Nahdlatul Ulama (NU), Muhammadiyah and Islamic Unity/ Persatuan Islam (Persis) in Sapeken, Sumenep-Madura and economy strategy played by Persis as the majority in the midst of NU's domination. This research is unique because of several reasons, 1) Sumenep-Madura is the basis of NU and Muhammadiyah, 2) Persis is able to shift those two religious organizations. In several studies, the Madurese community is more highlighted with nuances of nahdliyin, but the depiction of conditions in Sapeken is different and inversely proportional. Therefore the current researcher offers a synthesis by raising the idea that Persis's power lies in the politic-economy strategy. In order to be more systematic, this research used qualitative with a descriptive analysis approach. The data taken was only primary sources by involving directly to the field through interview techniques and non-participatory observation. The data were later analyzed. A number of essential results were found, first, the strategy used to shift the traditionalist religious sects was perusing the parts of the people-base economy unempowered by NU and Muhammadiyah. Second, the religious-based politic-economy played by Persis controled the micro-macro economic development. Third, the structures controlled as a form of religious-political economy were economic and educational aspects.  Penelitian ini mendeskripsikan fenomena kontestasi aliran keagamaan Nahdlatul Ulama (NU), Muhammadiyah dan Persatuan Islam (Persis) di Sapeken, Sumenep-Madura dan strategi ekonomi yang dimainkan oleh Persis sebagai mayoritas di tengah dominasi NU. Penelitian ini unik karena beberapa alasan, 1) Sumenep-Madura adalah basis NU dan Muhammadiyah, 2) Persis mampu menggeser kedua organisasi keagamaan tersebut. Dalam beberapa penelitian, masyarakat Madura lebih ditonjolkan dengan nuansa nahdliyin, namun penggambaran kondisi di Sapeken berbeda bahkan berbanding terbalik. Untuk itu peneliti saat ini menawarkan sintesa dengan mengangkat gagasan bahwa kekuatan Persis terletak pada strategi ekonomi politik yang dimainkan. Agar lebih sistematis, penelitian ini menggunakan kualitatif dengan pendekatan analisis deskriptif. Data yang diambil hanya sumber primer dengan terjun langsung ke lapangan melalui teknik wawancara dan observasi non partisipatif. Setelah itu, langkah-langkah menganalisis data, ditemukan beberapa hasil penting, yaitu pertama strategi yang digunakan untuk menggeser aliran keagamaan tradisionalis dengan menyisir bagian-bagian ekonomi kerakyatan yang belum tersentuh oleh NU dan Muhammadiyah. Kedua, politik ekonomi berbasis agama yang dimainkan Persis mengontrol sisi pembangunan mikro-makro ekonomi. Ketiga, struktur yang dikuasai sebagai bentuk ekonomi politik keagamaan adalah aspek ekonomi dan aspek pendidikan.